Students’ perceptual quality standards for judging knowledge quality: Development and validation of a perceived e-learning knowledge quality scale - Waheed, Mehwish; Kaur, Kiran (SAGE Publications, 2019)
This study examines the factors contributing towards eLearning knowledge quality based on students’ perspective and presents a 5-dimensional scale to evaluate knowledge quality (KQ). It is an extension of our previously published research which had proposed a novel conceptual KQ model. In this paper, we attempt to quantify knowledge quality (KQ), as opposed to adapting data quality (DQ) and information quality (IQ) measurement tools. A qualitative-quantitative sequential mixed-method design was used for the instrument validation. Data was collected at two levels, undergraduate and postgraduate respectively. Exploratory and confirmatory factor analysis confirmed the 5 dimensional second-order perceived eLearning KQ model – comprising of 33 sub-dimensions. The scale is inclusive of five key dimensions (Intrinsic KQ, Contextual KQ, Representational KQ, Accessible KQ, and Actionable KQ) as measures of quality of knowledge gained from eLearning content. The proposed dimensions are the benchmarks that provide insight to educators and administrators in developing and enhancing e-learning content. © The Author(s) 2017.